2013
DOI: 10.1590/s0100-40422013000200007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of essential oils of Lippia sidoides and Lippia gracilis and their major chemical components against Thielaviopsis paradoxa, causal agent of stem bleeding in coconut palms

Abstract: ). L. sidoides oil contained 42.33% thymol and 4.56% carvacrol, while L. gracilis oil contained 10% thymol and 41.7% carvacrol. Mycelial growth and conidial production of T. paradoxa were completely inhibited by thymol at a 0.3 μL m -1 concentration. The results suggest that thymol could potentially be used for controlling coconut stem bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 6 publications
1
11
0
2
Order By: Relevance
“…In L. sidoides oil, thymol (76.6%) and p‐cymene (6.3%) were the major compounds of the 21 identified, accounting for 98.6% of the total composition. These prevalent compounds were also found in L. sidoides oil analysed in other studies, with proportions varying as a function of cropping area (Oliveira, Moura, Lopes, Andrade, Silva & Figueiredo ; Cavalcanti, Niculau, Blank, Câmara, Araújo & Alves ; Farias‐Junior, Rios, Moura, Almeida, Alves, Blank, Fernandes & Scher ; Mota, Lobo, Costa, Costa, Rocha, Silva, Pohlit & Andrade‐Neto ; Carvalho, Laranjeira, Carvalho‐Filho, Souza, Blank, Alves, Jesus & Warwich ; Veras, Araruna, Costa, Coutinho, Kerntopf, Botelho & Menezes ). In contrast to our findings and most studies on this species, Lage, Montanari, Fernandes, Monteiro, Senra, Zeringota, Calmon, Matos and Daemon () reported carvacrol (31.9%) as the major component and thymol (30.6%) as the second most prevalent component in the essential oil of L. sidoides cropped in Araponga, MG.…”
Section: Resultssupporting
confidence: 64%
“…In L. sidoides oil, thymol (76.6%) and p‐cymene (6.3%) were the major compounds of the 21 identified, accounting for 98.6% of the total composition. These prevalent compounds were also found in L. sidoides oil analysed in other studies, with proportions varying as a function of cropping area (Oliveira, Moura, Lopes, Andrade, Silva & Figueiredo ; Cavalcanti, Niculau, Blank, Câmara, Araújo & Alves ; Farias‐Junior, Rios, Moura, Almeida, Alves, Blank, Fernandes & Scher ; Mota, Lobo, Costa, Costa, Rocha, Silva, Pohlit & Andrade‐Neto ; Carvalho, Laranjeira, Carvalho‐Filho, Souza, Blank, Alves, Jesus & Warwich ; Veras, Araruna, Costa, Coutinho, Kerntopf, Botelho & Menezes ). In contrast to our findings and most studies on this species, Lage, Montanari, Fernandes, Monteiro, Senra, Zeringota, Calmon, Matos and Daemon () reported carvacrol (31.9%) as the major component and thymol (30.6%) as the second most prevalent component in the essential oil of L. sidoides cropped in Araponga, MG.…”
Section: Resultssupporting
confidence: 64%
“…The activity of the essential oil of L. sidoides and L. gracilis and chemical components against the fungus Thielaviopsis paradoxa recently have been reported. The compounds p-cymene, 1.8 cineole, α-terpinene and β-caryophyllene had no efficiency when tested alone, and the authors proposed that they act in synergy with other compounds because the thymol concentration required to control the fungus was higher than the concentration of the L. sidoides essential oil (CARVALHO et al, 2013 Cruz et al (2013). Different letters represent significant differences among the essential oils or monoterpenes (p ˃ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a wide range of plant secondary metabolites exhibit antimicrobial properties, and these are often associated with the natural defense mechanism against attack by phytopathogenic bacteria and fungi (JANSSEN;SCHEFFER;BAERHEIM-SVENDSEN, 1987). In this context, a number of studies have shown that crude plant extracts and essential oils are potentially useful for controlling various types of phytopathogens (CARVALHO et al, 2013;RAHMAN;HOSSAIN;KANG, 2010;SILVA et al, 2012a;SILVA et al, 2012b;BASTOS 2007;VIGO-SCHULTZ et al, 2006).…”
Section: Introductionmentioning
confidence: 99%